The role of technology in the strategic planning of international companies: digital transformation and efficiency - Zaika, O.; Chubka, I. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2024)
Strategic planning in the modern world is becoming an integral and important management tool for international companies. This article examines the main aspects of strategic planning, defining its essence, features, and challenges faced by international companies in strategic planning. The study focuses on the strategic planning of international companies using modern technologies and analyses the impact of digital transformation on their activities. The main goal was to identify prospects and challenges in this area. The article reflects modern approaches to strategic planning, emphasizing the role of technology, in particular digital transformation, in the success of international companies in the world of challenges in the form of globalization and digitalization. The article provides an analysis of the concept of digital transformation, emphasizes its prospects and reveals its key role in the strategic planning of international companies. The study examines various technologies used in strategic planning and compares their functional and price characteristics. Highlighting the significance and impact of digital innovations on strategic planning, the article also offers an in-depth consideration of the possibilities of using modern technologies in decision-making and strategy development, in particular in the form of introducing analytical systems, to improve the efficiency of strategic and operational activities of international companies. The issue of digital transformation is explored, which allows for a more complete picture of the holistic impact of technology on companies' strategic decisions. Based on research of comparing analytical systems, the author concludes that effective digital transformation can significantly improve the strategic planning of international companies, providing them with competitive advantages and increasing their efficiency in the global business environment. Thus, consideration of digital transformation is becoming an integral part of successful strategic planning of international companies, contributing to their sustainable development and competitiveness.